Contributing to the understanding of Angiopolybia Araujo, 1946 (Hymenoptera, Vespidae, Polistinae): a new species, and descriptions of the nest of A. obidensis and male of A. zischkai - Barroso, Paulo Cézar Salgado; Somavilla, Alexandre; Broad, Gavin R.; Menezes, Rodolpho Santos Telles; Oliveira, Marcio Luiz De (Zootaxa, 2024)
Despite being a small genus, much remains unknown about the Neotropical social wasp genus Angiopolybia Araujo, 1946 (Polistinae: Epiponini). Here we describe the new species A. obscuriorina Barroso, sp. nov., the nest of A. obidensis (Ducke, 1904) and a hitherto unknown male of A. zischkai Richards, 1978.